Talking your iPhoto '11 to the max - Grothaus, Michael (Apress, 2011)
Taking your iPhoto '11 to the Max walks users through Apple's most popular software application in the iLife suite - iPhoto. This book helps readers use iPhoto to its fullest to organize and create digital memories and keepsakes. Learn all about Apple's newest version of iPhoto - iPhoto '11. Explore iPhoto, one menu button at a time. Walk-through tutorials guide you step-by-step.